Péče na prodej : jak se práce z lásky stává placenou službou - Souralová, Adéla (Masarykova univerzita, 2017)
What do kindergarten homeschools, dog hotels, hourly husbands, senior care, and babysitting and housekeeping services have in common? These are providers of paid services which, until recently, used to be given by loving household members to others for free. This book focuses on the current trend of the acts of "social reproduction" being moved from the private sphere of home and family to the public market. The authors present the findings of their qualitative research which has focused on the supply of this kind of services and their presentation to potential clients. The perspective of the providers, the owners of the agencies, is truly interesting. It offers an insight into the thinking and practice of people who actively take the wheel to drive us towards marketisation of our lives.